Hubungan Antara Minat Baca Terhadap Kemampuan Membaca Pemahaman Siswa Kelas V SD Gugus I Kecamatan Ulaweng Kabupaten Bone - Satriani, Satriani (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
The problem studied in this study was the relationship between reading interest and reading comprehension ability of fifth-grade students at SD Gugus 1, Ulaweng District, Bone Regency. This study is a correlation study that aims to determine the description of reading interest, the description of reading comprehension ability, and the relationship between reading interest and reading comprehension ability in fifth-grade students at SD Gugus I, Ulaweng District, Kab. Bone. A research approach is a quantitative approach. This type of research is a correlation study. The research data were obtained through questionnaires and tests. The population in the study were all fifth-grade students of SD Gugus I, Ulaweng District, Bone Regency, in the 2019/2020 academic year totaling 111 students. The sample in the study amounted to 58 students. The data analysis technique is a descriptive statistical analysis and correlation analysis. The results showed that the reading interest of the fifth-grade students of SD Gugus I, Ulaweng District, Bone Regency was in the high category, and the reading comprehension ability of the fifth-grade students of SD Gugus I Elementary School, Ulaweng District, Bone Regency was in the medium category and there was a significant relationship between reading interest and the students' reading comprehension ability class V.